HaCaT Keratinocytes Response on Antimicrobial Atelocollagen Substrates: Extent of Cytotoxicity, Cell Viability and Proliferation - López-García, Jorge; Lehocký, Marián; Humpolíček, Petr; Sáha, Petr (Journal of functional biomaterials, 2014)
The effective and widely tested biocides: Benzalkonium chloride, bronopol, chitosan, chlorhexidine and irgasan were added in different concentrations to atelocollagen matrices. In order to assess how these antibacterial agents influence keratinocytes cell growth, cell viability and proliferation were determined by using MTT assay. Acquired data indicated a low toxicity by employing any of these chemical substances. Furthermore, cell viability and proliferation were comparatively similar to the samples where there were no biocides. It means that regardless of the agent, collagen-cell-attachment properties are not drastically affected by the incorporation of those biocides into the substrate. Therefore, these findings suggest that these atelocollagen substrates enhanced by the addition of one or more of these agents may render effectiveness against bacterial stains and biofilm formation, being the samples referred to herein as "antimicrobial substrates" a promising view in the design of novel antimicrobial biomaterials potentially suitable for tissue engineering applications.